Strategi Panti Asuhan SOS Children’s Villages Meulaboh dalam Menjamin Perlindungan Anak Terlantar - Mutia , Riska Intan; Hajad, Vellayati; Ikhsan, Ikhsan (Journal of Social Politics and Governance (JSPG), 2023)
This study examines the protection of abandoned children from one of the social institutions, namely SOS Children's Villages Meulaboh. This study aims to determine the success of the protection program for neglected children at SOS Children's Villages Meulaboh. This study uses a qualitative method with a case study approach. Data collection techniques using observation, interviews, documentation, and audio-visual materials. The results of this study indicate that child protection at the SOS Children's Villages Meulaboh orphanage has been running well and properly. Through programs designed for the protection of children to ensure the fulfillment of their rights so that they can live, grow and develop like children in general, and are protected from violence and discrimination. In addition, SOS also organizes/provides various activities that support children's growth and development. This is useful for developing religious moral abilities, academic abilities, ethics/politeness so that the realization of quality and noble children.